2022
DOI: 10.2147/cmar.s358054
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Prostate Cancer Patients Undergoing Prostatectomy and Affective Temperament

Abstract: Purpose Prostate cancer (PC) is one of the most common malignancies in men. The population of PC survivors is growing, and understanding the roles of different factors that affect quality of life (QoL) is important. We investigated the effects of affective temperament on the QoL of PC patients. Patients and Methods All subjects (n=100) underwent medical evaluation [including demographic data, medical history, physical examination, biochemical tests, and assessment of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Popiołek et al, (2022) showed that depressive, cyclothymic irritable and anxious temperaments measured by TEMPS-A are associated with decreased quality of life in this clinical group. 40 Moreover, affective temperaments were associated with worse urinary symptoms, worse sexual functioning, occurrence of postoperative complications, as well as with more severe anxiety and depressive symptoms. Those results suggest that temperamental features and mood disturbances associated with bipolar spectrum may have an impact on prostate cancer patients psychological functioning and somatic symptoms.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Popiołek et al, (2022) showed that depressive, cyclothymic irritable and anxious temperaments measured by TEMPS-A are associated with decreased quality of life in this clinical group. 40 Moreover, affective temperaments were associated with worse urinary symptoms, worse sexual functioning, occurrence of postoperative complications, as well as with more severe anxiety and depressive symptoms. Those results suggest that temperamental features and mood disturbances associated with bipolar spectrum may have an impact on prostate cancer patients psychological functioning and somatic symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…Our results corroborate with the study evaluating the role of temperamental features connected to bipolar disorder in the prostate cancer patients' group. Popiołek et al., (2022) showed that depressive, cyclothymic irritable and anxious temperaments measured by TEMPS‐A are associated with decreased quality of life in this clinical group 40 . Moreover, affective temperaments were associated with worse urinary symptoms, worse sexual functioning, occurrence of postoperative complications, as well as with more severe anxiety and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a study conducted by Kurian et al [ 33 ], which examined age and QoL among prostate cancer patients reported that old age negatively affected health-related quality of life. The study performed by Popiołek et al [ 34 ] also found advanced age reduced QoL among prostate cancer surgery patients.…”
Section: Discussionmentioning
confidence: 96%
“…Gondoputro et al observed higher rates of moderate/big bother in younger patients (<55 years) when using >1 pad/24 h, compared to older patients [ 18 ]. Moreover, for younger men, a greater social stigma for pad usage could result in even more increased concomitant anxiety [ 26 , 27 ]. In line with these observations, Ilie et al identified older age as a protective factor for screening positive for mental distress in prostate cancer patients treated with radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%